Mining Medical Data: A Comprehensive Study - Krishna, Rama K; Mohan, KG (International Journal of Computer Sciences and Engineering, 2025)
Health care industry generates huge volumes of data that comprises of complex information pertaining to patients’ data and their medical history. Data mining methodologies have the abilities to discover hidden patterns and associations among the attributes in the medical dataset. Due to Data Mining’s enormous applications, there has been an upsurge in usage of data mining techniques on medical data for discovering useful trends or knowledge patterns that are used in strategic decisionmaking process or disease diagnosis and treatment process. This paper focuses on need for mining medical data, issues and challenges surrounding Mining Medical Data.